Clinical evaluation of photodynamic therapy for oral leukoplakia: a retrospective study of 50 patients - Yanting Wang; Haonan Tang; Keyi Wang; Yuping Zhao; Juanyong Xu; Yuan Fan (BMC, 2024)
Abstract Background Topical photodynamic therapy (PDT) has demonstrated encouraging results in the treatment of oral leukoplakia (OLK). However, data on the clinical efficacy of PDT in Chinese patients with OLK are still limited. Methods Fifty patients diagnosed with OLK were enrolled, including patients with various dysplastic tissues. All patients received topical PDT with 5-aminolevulinic acid (5-ALA) as a photosensitizer. Clinical efficacy was evaluated 4 weeks after treatment. Follow-up was performed every 3 months during the first year and every 6 months during the second year. Results The overall response rate was 68% (34/50): 12% (n = 6) complete and 56% (n = 28) partial responses. Aneuploidy was reduced in the patients with dysplastic lesions. Oral pain and local ulcers developed in 52% of the patients (n = 26). Patients with a long history of OLK including hyperplasia and dysplastic lesions, as well as those with non-homogenous lesions, were more likely to develop pain and ulcer. During follow-up, the recurrence rate of hyperplasia and dysplastic lesions was 32% (n = 16) and the malignant transformation rate of dysplastic lesions was 4% (n = 2). Lesions on the buccal mucosa were associated with recurrence (P = 0.044; OR: 0.108, 95% CI: 0.013-0.915). Conclusion Topical 5-ALA-mediated PDT is an effective treatment for OLK, particularly for homogenous leukoplakia, with few side effects. The buccal mucosa may be a protective factor that can reduce recurrence.